2014
DOI: 10.1007/s10071-014-0780-x
|View full text |Cite
|
Sign up to set email alerts
|

Who’s watching influences caching effort in wild Steller’s jays (Cyanocitta stelleri)

Abstract: Steller's jays (Cyanocitta stelleri) often store food and return to retrieve the stored items at a later time. Between caching and consumption, stored food has the potential to be pilfered by conspecific observers. We investigated whether individually marked Steller's jays in suburban neighborhoods of Arcata, California, USA, adjusted cache concealment effort when in the presence of conspecifics. Both male and female jays traveled the shortest distances to cache when alone, traveled further when a mate was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Thus, Eurasian jays seem to engage in a variety of different behaviour that might function to minimise cache loss. The results also suggest that caching at a distance to a conspecific is present in a range of caching corvid species (Bugnyar and Kotrschal 2002 ; Dally et al 2005 ; Kalinowski et al 2015 ). A potential exception to this finding is the Clark’s nutcracker.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Thus, Eurasian jays seem to engage in a variety of different behaviour that might function to minimise cache loss. The results also suggest that caching at a distance to a conspecific is present in a range of caching corvid species (Bugnyar and Kotrschal 2002 ; Dally et al 2005 ; Kalinowski et al 2015 ). A potential exception to this finding is the Clark’s nutcracker.…”
Section: Discussionmentioning
confidence: 65%
“…Ravens ( Corvus corax ), Western scrub-jays and Steller’s jays ( Cyanocitta stelleri ) also preferentially cache at distant locations when conspecifics are present (Dally et al 2005 ; Kalinowski et al 2015 ). This behaviour has been interpreted as an attempt to limit the observer’s visual access to the caching event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species have strategies to reduce pilferage by conspecifics (Bugnyar and Kotrschal 2002, Dally et al 2006a, Clayton et al 2007), but behavioral responses may vary with the social context of observers at the time of caching (Pravosudov and Lucas 2000). Some species modify their caching behavior depending on the social or dominance status of nearby observers (Lahti et al 1998, Dally et al 2006b, Kalinowski et al 2015). When observed during caching, some may prefer to cache in private by flying farther (Dally et al 2005), caching behind screening vegetation (Legg and Clayton 2014), or re‐caching an item when no longer being observed (van der Vaart et al 2012).…”
mentioning
confidence: 99%
“…Previous caching studies have demonstrated that caching and its related behaviours can vary in different social environments (Alexander et al, 2005;Bugnyar & Heinrich, 2006;Kalinowski, Gabriel, & Black, 2015;Van Horik & Burns, 2007). For instance, adult robins from the same population as this study, have been shown to dramatically decrease their caching rates in the presence of their mate compared to when they are alone (Burns & Steer, 2006).…”
Section: Future Directionsmentioning
confidence: 57%